Writing with children s: a possibility of co-authorship in ethnographic research - Diana Milstein (Editora da Universidade de Santa Cruz do Sul, 2010)
: This article shows how two groups of children of a primary school in a town in southern suburbs of Buenos Aires, Argentina, were included as interlocutors, interviewers, observers and co-writers in my ethnographic fieldwork, during 2004 and 2005. We published two booklets with the children in cooperation. They contain versions of the "others" and of the authors about the town. Both of them brought together a polyphonic set of stories and comments, along with the opinions of adults, youths and children from various ages, origins, families and occupations. The booklets provide intelligible versions of local social life by using a descriptive and narrative style and include maps drawn by children and photographed images. I develop an analysis of the particularities of the co-authorship with these children through an account of these work processes and the production of booklets. Then I discuss agency of children in aspects relate with their capacities as interpreters and authores and I propose innovative and creative ways to interact with children. Finally I argue that these modes can also impact educational processes. Keywords: ethnography; fieldwork; children as co-writers; educative experience